2002
DOI: 10.1143/jjap.41.3579
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging (MRI) Compatible Ultrasound Therapeutic System

Abstract: We present a portable instrument for a comprehensive particle and particle motion analysis for a large variety of applications. The instrument presently exists as a prototype. It combines two optical techniques which were originally developed for astrophysically-motivated laboratory research. One is based on bright-field microscopy to image micrometre-sized particles and to give structural information. The other is based on stroboscopic trajectory imaging to yield the motion of particles. The latter is applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It is difficult to examine the region to be ablated by conventional ultrasonography. Magnetic resonance imaging (MRI) is also useful in demonstrating the extent of damaged tissue [1]. T2-weighted images show regions of tissue necrosis clearly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to examine the region to be ablated by conventional ultrasonography. Magnetic resonance imaging (MRI) is also useful in demonstrating the extent of damaged tissue [1]. T2-weighted images show regions of tissue necrosis clearly.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is a useful technique for following the progress of tissue destruction in vivo following ultrasound exposure. It has also been shown that tissue volumes in which the temperature is elevated can be visualized using MRI [1]. HIFU in combination with an MRI system may be used in the future in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…High intensity focused ultrasound (HIFU) is attracting interest as a new modality for treating a tumor. [1][2][3][4] A HIFU system needs to transmit a higher time-average ultrasonic power than an ultrasound imaging system, and a common practice is to use a piezoelectric transducer to generate ultrasound waves. An important component of the system is high-voltage drivers to excite such a transducer, which typically consists of a number of array elements.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic medical equipment is used in not only diagnosis but also therapy such as that for treating hyperthermia. Highintensity focused ultrasound (HIFU) 1) is a typical application using high-power ultrasound. Many researchers are also studying high-frequency ultrasonic imaging systems with interluminal or catheter transducers.…”
Section: Introductionmentioning
confidence: 99%